(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
acceptance sampling plan was adopted to study mainly for valid conclusions with regard to consideration accept or reject of the finished products. In this way numbers of optimal techniques were developed to increase and control the quality of the products. Basing on the assumption the variable with regard to quality characteristic is distributed accordingly to certain probability law. In our study we optimized CASP-CUSUM Schemes based on the assumption that the continuous variable which is under the consideration follows a Truncated Expoentiated Gompertz distribution utilized in Statistical Quality Control and Reliability analysis. In particular the distribution is meant for estimating the optimal truncated point and probability of acceptance of lot. The operating characteristic and Average run length values are presented. The results are illustrated by figures.